Present and future of the Educational Inspection - Bar Cendón, José Manuel; Martínez Muñoz, Francisco (Avances en Supervisión Educativa, 2018)
The paper we are about to expose starts from ADIDE Federation hallmark, which is based upon the principles of professional independence, transparency and public service. It carries on with a comparative study of the basic and regional current laws regarding the Inspectorate, essentially analyzing the presence of the aforementioned principles along them. Finally, our paper draws up some proposals to improve the situation starting from the previous data and conclusions, the Inspectorate status in other countries, and the implementation of the role of the Inspectorate as an organ officially recognized by the Organic Law of Education. In the end, our paper outlines the development of the compliance of the Spanish Constitution (art. 27.8): "The public authorities will inspect and homologate the Education System...", by means of proposals based upon the connection, commitment, work and collaboration with the executive, legislative and judicial branches.